Electrochemical CO2 Reduction in the Presence of Impurities: Influences and Mitigation Strategies. (17th November 2022) - Harmon, Nia J.; Wang, Hailiang
Abstract: The electrochemical conversion of waste CO2 into useful fuels and chemical products is a promising approach to reduce CO2 emissions; however, several challenges still remain to be addressed. Thus far, most CO2 reduction studies use pure CO2 as the gas reactant, but CO2 emissions typically contain a number of gas impurities, such as nitrogen oxides, oxygen gas, and sulfur oxides. Gas impurities in CO2 can pose a significant obstacle for efficient CO2 electrolysis because they can influence the reaction and catalyst. This Minireview highlights early examples of CO2 reduction studies using mixed‐gas feeds, explores strategies to sustain CO2 reduction in the presence of gas impurities, and discusses their implications for future progress in this emerging field. Abstract : Power plants release CO2 and gaseous impurities into the atmosphere. In recent years, the effect of gaseous impurities on CO2 electrolysis has emerged as an important research topic, with an emphasis placed on understanding the catalytic reaction and developing mitigation strategies to lessen the negative effects of gaseous impurities.